600 small-scale tree nurseries in Burkina Faso hold large diversity - Vinceti, Barbara; Mattson, Sean (2024)
Tree diversity in Burkina Faso’s large, informal network of community nurseries is encouragingly high, providing a key resource for ambitious restoration plans. Funding and technical support is needed to improve seed quality, genetic diversity, seed sourcing and management of planting material. Findings support the implementation of a large-scale capacity-building program aimed at improving the quality and diversity of tree-planting materials provided by small-scale nurseries. The new research is part of a growing body of work on native tree systems in Burkina Faso and other African nations by the Alliance of Bioversity International and CIAT and other CGIAR centers